Structure-Function Analysis of the GlyR α2 Subunit Autism Mutation p.R323L Reveals a Gain-of-Function - Zhang, Yan; Ho, Thi Nhu Thao; Harvey, Robert J.; Lynch, Joseph W.; Keramidas, Angelo (Frontiers in Molecular Neuroscience, 2017)
Glycine receptors (GlyRs) containing the α2 subunit regulate cortical interneuron migration. Disruption of the GlyR α2 subunit gene (Glra2) in mice leads to disrupted dorsal cortical progenitor homeostasis, leading to a depletion of projection neurones and moderate microcephaly in newborn mice. In humans, rare variants in GLRA2, which is located on the X chromosome, are associated with autism spectrum disorder in the hemizygous state in males. These include a microdeletion (GLRA2Δex8-9) and missense mutations in GLRA2 (p.N109S and p.R126Q) that impair cell-surface expression of GlyR α2, and either abolish or markedly reduce sensitivity to glycine. We report the functional characterization of a third missense variant in GLRA2 (p.R323L), associated with autism, macrocephaly, epilepsy and hypothyroidism in a female proband. Using heterosynapse and macroscopic current recording techniques, we reveal that GlyR α2R323L exhibits reduced glycine sensitivity, but significantly increased IPSC rise and decay times. Site-directed mutagenesis revealed that the nature of the amino acid switch at position 323 is critical for impairment of GlyR function. Single-channel recordings revealed that the conductance of α2R323Lβ channels was higher than α2β channels. Longer mean opening durations induced by p.R323L may be due to a change in the gating pathway that enhances the stability of the GlyR open state. The slower synaptic decay times, longer duration active periods and increase in conductance demonstrates that the GlyR α2 p.R323L mutation results in an overall gain of function, and that GlyR α2 mutations can be pathogenic in the heterozygous state in females.